A tale of two skeletons? - Kennedy, Scott (Byzantinische Zeitschrift, 2021)
The body of almost every Roman or Byzantine emperor has been lost. This piece draws attention to two skeletons, recovered from a Muslim türbe at Trabzon during World War I by the Russian excavator Feodor Uspensky. Using local oral tradition, Uspensky identified the two bodies he recovered as the Byzantine emperor of Trebizond Alexios IV (1417-1429) and a local Turkish hero Hoşoğlan. Since Uspensky, his identifications have not been challenged nor scientifically examined. This paper argues that Uspensky did not recover just one but two imperial skeletons. It first dissects his identifications, showing how competition for sacred space between Greeks and Turks in the Ottoman period led each community to identify the tomb’s occupants with foundational figures in their communities. After dissecting Uspensky’s identifications, this paper then makes the case that both occupants of this tomb were unidentified members of the Grand Komnenoi family, urging for scientific examination of what may be the only bones of a Byzantine emperor.